Enhanced stability of thin film transistors with double-stacked amorphous IWO/IWO:N channel layer. (25th April 2018) - Lin, Dong; Pi, Shubin; Yang, Jianwen; Tiwari, Nidhi; Ren, Jinhua; Zhang, Qun; Liu, Po-Tsun; Shieh, Han-Ping
Abstract: In this work, bottom-gate top-contact thin film transistors with double-stacked amorphous IWO/IWO:N channel layer were fabricated. Herein, amorphous IWO and N-doped IWO were deposited as front and back channel layers, respectively, by radio-frequency magnetron sputtering. The electrical characteristics of the bi-layer-channel thin film transistors (TFTs) were examined and compared with those of single-layer-channel (i.e., amorphous IWO or IWO:N) TFTs. It was demonstrated to exhibit a high mobility of 27.2 cm 2 V −1 s −1 and an on/off current ratio of 10 7 . Compared to the single peers, bi-layer a-IWO/IWO:N TFTs showed smaller hysteresis and higher stability under negative bias stress and negative bias temperature stress. The enhanced performance could be attributed to its unique double-stacked channel configuration, which successfully combined the merits of the TFTs with IWO and IWO:N channels. The underlying IWO thin film provided percolation paths for electron transport, meanwhile, the top IWO:N layer reduced the bulk trap densities. In addition, the IWO channel/gate insulator interface had reduced defects, and IWO:N back channel surface was insensitive to the ambient atmosphere. Overall, the proposed bi-layer a-IWO/IWO:N TFTs show potential for practical applications due to its possibly long-term serviceability.